2020
DOI: 10.1097/iae.0000000000002760
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Characteristics of Polypoidal Choroidal Vasculopathy Based on B-Scan Swept-Source Optical Coherence Tomography Angiography and Its Interrater Agreement Compared With Indocyanine Green Angiography

Abstract: Purpose: To examine the characteristics of polypoidal choroidal vasculopathy using B-scan optical coherence tomography angiography (OCTA), and determine the diagnostic criteria of polypoidal choroidal vasculopathy based on OCTA. Methods: This retrospective case series included patients diagnosed with treatment-naïve polypoidal choroidal vasculopathy who underwent indocyanine green angiography (ICGA) and swept-source OCTA at baseline. We compared the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…This latter group may be further classified into exudative, hemorrhagic, or mixed. Clinically, the exudation comes in the form of either serous PED, subretinal fluid, serous macular detachment, subretinal lipid exudation, or intraretinal fluid, whereas hemorrhagic PCV presents with subretinal or subretinal pigment epithelium (RPE) hemorrhage [6].…”
Section: Introductionmentioning
confidence: 99%
“…This latter group may be further classified into exudative, hemorrhagic, or mixed. Clinically, the exudation comes in the form of either serous PED, subretinal fluid, serous macular detachment, subretinal lipid exudation, or intraretinal fluid, whereas hemorrhagic PCV presents with subretinal or subretinal pigment epithelium (RPE) hemorrhage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography angiography (OCTA) allows the identification of PCV with a high accuracy and can replace traditional invasive indocyanine green angiography (ICGA) [4,13,14]. In the last years, several studies showed the efficacy of intravitreal injections of vascular endothelial growth factor (VEGF) antagonists for the treatment of PCV [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional SS-OCTA revealed abnormal flow in another 23 of 32 eyes (71.9%) without MNV illustration in en-face SS-OCTA ( Figure 1 B3). The superiority of combining en-face SD-OCTA and cross-sectional SD-OCTA as opposed to en-face SD-OCTA alone in patients with nAMD or PCV has been reported previously [ 28 30 ]. Thus, the overall sensitivity of the MNV detection rate in SS-OCTA increased to 94.3% as compared to dye-based angiography.…”
Section: Discussionmentioning
confidence: 74%